The development of the horticultural industry in Namibia : an assessment of the determinants of the global market competitiveness of table grape production - Thomas, Benisiu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2007.